DEVELOPMENT OF STEAM-BASED LEARNING MEDIA THROUGH LESSON STUDY FOR ELEMENTARY SCHOOL TEACHERS - Sheryl Mutiara Putri; Rinaldi Yusup; Sajidin; Rahmat Hidayat (Jurnal Cakrawala Pendas, 2024)
This study aims to develop STEAM (Science, Technology, Engineering, Arts, and Mathematics)-based learning media with a lesson study approach to improve the quality of learning in Elementary Schools in Cisolok District. The method used in this study is development (Research and Development/R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. In the analysis stage, student needs and STEAM challenges are identified through initial observations and interviews. The media design is prepared based on the results of the analysis, and developed through a prototype that is tested in class. Implementation is carried out in Elementary Schools in Cisolok District, with data collection through observation, questionnaires, and interviews to measure student and teacher responses to the media developed. The collected data are analyzed quantitatively and qualitatively, using descriptive statistics for questionnaires, and qualitative analysis of interviews to understand teacher experiences and challenges in lesson study. Statistical tests are conducted to evaluate changes in student engagement and improvements in teacher competence. The results of the study indicate that the developed STEAM-based learning media can increase student engagement in the learning process. In addition, teacher collaboration in lesson study has proven effective in improving teacher professional competence, especially in designing and implementing innovative learning media. This study contributes to the development of learning media that are more relevant to students' needs and provides solutions to challenges in STEAM-based learning in elementary schools.